The Prison to Homelessness Pipeline: Criminal Record Checks, Race, and Disparate Impact - Schneider, Valerie (2018)
Study after study has shown that securing housing upon release from prison is critical to reducing the likelihood of recidivism,1 yet those with criminal records— a population that disproportionately consists of racial minorities—are routinely denied access to housing, even if their offense was minor and was shown to have no bearing on whether the applicant would be likely to be a successful renter. In April of 2016, the Office of General Counsel for the United States Department of Housing and Urban Development (HUD) issued much anticipated guidance dealing directly with the racially disparate impact of barring those with criminal records from public and private housing. After decades of seeming to encourage local public housing providers to adopt harsh policies barring applicants with criminal records regardless of the nature or recency of the crime, the Obama-era guidance from HUD represents a sea change in federal policy and will force local housing authorities to grapple with the potentially disparate impacts of harsh criminal record policies. The guidance is particularly timely, given that HUD issued a rule clarifying the burden of proof in disparate impact cases in 20132 and the Supreme Court affirmed that disparate impact claims are cognizable under the Fair Housing Act in its 2015 decision in Texas Department of Housing & Community Affairs v. Inclusive Communities Project, Inc.3 Additionally, while the Trump administration seems focused on rolling back Obama-era protections in some arenas, this guidance has remained in place. Even if withdrawn by HUD, the guidance has already inspired local policies restricting the use of criminal background checks in housing decisions potentially giving rise to a new era for those seeking housing after being released from prison.4 This Article first puts the problem of using criminal records to evaluate potential tenants into historical context, discussing the particular impact of the rising rates of incarceration on minority communities. Next, the Article delves into the guidance itself, examining what it does and does not require of housing providers, with a focus on public housing. Finally, the Article provides insight into what is missing from the guidance, what might be done to strengthen it, how advocates might use it, and how housing providers might work to limit both their legal exposure and moral culpability related to the disparate impact the use of criminal records in housing decisions has on minorities